Pemikiran Tasawuf Anregurutta H. Abdurahman Ambo Dalle - Mursalim Mursalim (FENOMENA, 2015)
This research wants to know proprietary tasawuf thinking by Anregurtta H. Abdurrahman Ambo Dalle (called Ambo Dalle) in his book in Bugis's lingual version “al Qawl al shadiq li Ma ’ rifat al Khaliq / ada tongeng tongengnge ri annessana pappejeppue ri puang pancajie“. Thus, this research is bibliographical observational type (library research) one that gets character descriptive analysis. Anregurutta Abdurrahman Ambo Dalle is constitute ulama's figure that combine among knowledge syariat and tasawuf's knowledge. Harmony who did by Anregurutta among knowledge syariat with reality knowledge is an effort for unbent tarekat's concept or flow (tasawuf) one that amends, notably on Bugis's society who restrains from al Qur'an and hadits. That thing is looked while Anregurutta combine among bodily religious service and spritual religious service, one that religious service comes into the world is territorial temporary carnal job religious service, spritual is territorial heart job which is as recitation (remember) to God and that is core than religious service in Islamic. Such too its criticism to tasawuf's teaching with concept ittihad and hulul,  which is a concept that teaches one to declare for self a slave until to its The Infinite upon remembers (recitation) and at that moment as one with God, therefore expression “العابد والمعبود واحد “ while Anregurutta Ambo Dalle is “ العابد واحد والمعبود واحد ”